Dynamics and variation of regional firm formation - case of turkey- - Karahasan, Burhan Can (My University, 2010)
lgesel farklılıklar, firma oluşumu, mekansal analiz, mekansal ekonometri, panel veri modelleri ÖZET FİRMA OLUŞUMUNUN BÖLGESEL FARKLILAŞMASI VE DİNAMİKLERİ - TÜRKİYE ÖRNEĞİ - Bu tez Türkiye’de bölgesel farklılıkları üretimin mekan seçme davranışı üzerinden incelemeyi hedeflemiştir. Yeni firma sayıları ile tanımlanan üretimin mekan seçme davranışının bölgesel dağılımı ve bu dağılımın arkasında yatan sosyo-ekonomik nedenler il bazından incelenmiştir. Yeni coğrafya iktisadının kuramsal altyapısı ve bilgi yayılımı üzerinden çalışan girişimci bazlı büyüme modelleri kullanılmıştır. İlk bulgular firma oluşumunun, üretimin mekan seçme davranışının, Türkiye’nin coğrafyasında eşit olmayan bir şekilde dağıldığını göstermektedir. Bu dağınık yapı panel veri yöntemleri ile incelenmiştir. Tez çalışmasının sonuçları yerel talep, mali derinleşme ve eğitim kalitesinin firmaların mekan seçme davranışını etkilediğini göstermiştir. Buna ek olarak sektörel etkileşimin geçerli olmadığı, üretimin genel olarak aynı sanayi kollarına yakın mekan seçmeyi tercih ettikleri tespit edilmiştir. Son olarak mekansal oto korelasyon ve coğrafyanın rolü incelenmiştir. Bulgular Türkiye’de üretimin mekan seçme davranışında şiddetlenen bir mekansal heterojenlik olduğunu; firma oluşumu açısından gelişmiş bölgelerin daha çok geliştiği ve az gelişmişlerin az geliştiği bir yapının oluştuğunu göstermektedir. Bu bulgular coğrafyanın rolünün analiz edilmesi ile pekiştirilmiş ve üretimin piyasa potansiyelinin yüksek olduğu bölgeleri tercih ettiği tespit edilmiştir. Genel olarak tezin sonuçları Türkiye’de yeni firma oluşum sürecinin bölgeler arasında eşit dağılmadığı ve bu yapının Türkiye’deki genel bölgesel farklıklar ile benzer bir yapıya sahip olduğu vurgulamaktadır. Start up, regional differences, spatial analysis, spatial econometrics, panel data models

DYNAMICS AND VARIATION OF REGIONAL FIRM FORMATION - CASE OF TURKEY - This dissertation aims to scrutinize the regional inequalities in Turkey from the view point of location choice of production. Location choice of production, measured by the number of new firms in different industries, is examined and its variation is explained by focusing on the social and economical properties of provinces. Theoretical insights offered by new economics of geography as well as contemporary discussion of knowledge based entrepreneurial models are used. Preliminary results about the variation of new firm start ups indicate that location choice of production is unequal among the geography of Turkey. The unequal dispersion of firm formation is linked with the regional differences via different panel data models. Overall findings of the dissertation confirm that local demand, financial development and human capital quality act as pull effects for the location choice of production. Meanwhile additional findings indicate that industrial interactions are not existent, that the firms in specific industries prefer to locate close to same industries. Finally further impact of spatial autocorrelation as well as role of geography is observed. Results validate that there is increasing spatial heterogeneity in location choice of production; leaving developed provinces more developed and less developed provinces less developed in terms of firm formation. This finding is also confirmed by investigation of the role of geography; that production prefers to locate in high market access areas of the western geography of Turkey. In general results of the dissertation pinpoints that, dispersion of the location choice of production is unequal among the provinces of Turkey and this dispersed picture shares the common pattern realized in regional inequalities in Turkey.
Keywords: Bölgesel Farklılıklar; Ekonomi